Pengaruh Price Fairness Dan Servicecape Terhadap Repurchase Intention Pada Cafe Di Kota Sorong - Frisayanti , Fadia; Sofia, Susetyowati; Rahayu, Agilistya; Hasrun, Andi (PT. Karya Inovatif Nusantara, 2025)
The purpose of this study was to determine the effect of price fairness and servicescape on repurchase intention at cafes in Sorong City, West Papua. The research method uses quantitative methods, the data obtained is based on the answers of 123 respondents to the questionnaire, the sample was taken using purposive sampling technique with the criteria that they have visited a café in Sorong city. The data analysis technique uses validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple regression test, t test, F test, and determination coefficient test. The results of this study indicate that price fairness and servicecape have a positive and significant effect on repurchase intention.